2011
DOI: 10.5352/jls.2011.21.9.1205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Statistical Methods for Optimization of Salts in Medium for Production of Carboxymethylcellulase of Bacillus amyloliquefaciens DL-3 by a Recombinant E. coli JM109/DL-3

Abstract: The optimal concentrations of salts in medium for cell growth and the production of carboxymethylcellulase (CMCase) by a recombinant E. coli JM109/DL-3 were established using two statistical methods: orthogonal array method (OAM) and response surface method (RSM). The analysis of variance (ANOVA) of data based on OAM indicated that K2HPO4 gave maximum sum of square (S) and percentage contribution (P) for cell growth as well as production of CMCase. The optimal concentrations of K2HPO4, NaCl, MgSO4•7H2O, and (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The ANOVA indicated that this model and the model term of X1 ("probe > F" less 0.0001) were highly significant [23].…”
Section: Resultsmentioning
confidence: 88%
“…The ANOVA indicated that this model and the model term of X1 ("probe > F" less 0.0001) were highly significant [23].…”
Section: Resultsmentioning
confidence: 88%
“…The best carbon and nitrogen sources for cell growth of B. amyloliquefaciens DL-3 were sucrose and malt extract, whereas those for production of CMCase were rice hulls and peptone [22]. However, the best carbon and nitrogen sources for cell growth of its recombinant E. coli JM109/ DL-3 were fructose and ammonium chloride, whereas those for production of CMCase were rice bran and tryptone [23]. The best carbon and nitrogen source for cell growth and production of CMCase by B. subtilis subsp.…”
Section: Resultsmentioning
confidence: 96%
“…Those for production of CMCases by bacterial and fungal stains ranged from 25 to 37°C, except for thermophilic microorganisms such as Thermoascus aurantiacu, which optimal temperature for production of CMCase is 50°C [23]. The optimal temperature for the cell growth of a psychrophilic marine bacterium, P. aquimaris LBH-10 was lower than that for production of CMCase.…”
Section: Resultsmentioning
confidence: 99%
“…Potassium phosphate is one of major salts in the medium for productions of microbial polysaccharides and enzymes as well as a well-known ingredient in buffer solutions [13,23]. Sodium chloride was reported to be used as a physiological modulator of biosynthetic pathway of biopolymers [12,24]. Magnesium sulfate added to media assists with spore germination and initial growth of A. fisheri, which results in 1.9 fold increased production of xylanase [31].…”
Section: Optimization Of Salts In Medium For Production Of Cellobiasementioning
confidence: 99%
“…The optimization of culture medium by the traditional "one-factor-at-a-time" method requires a considerable amount of work and time. An alternative strategy is a statistical approach, for example, RSM involving a mini-mum number of experiments for a large number of factors [24].…”
Section: Introductionmentioning
confidence: 99%